Facile fabrication of TiO2/ZnO composite film anode by plasma electrolysis. (2nd December 2022) - Yang, Maolin; Lu, Ping; Zhang, Zhonghua; Chen, Lin; Qu, Yao; Wu, Jie
ABSTRACT: A TiO2 /ZnO composite film which served as the bind-free anode for lithium-ion battery was rapidly constructed on Ti foil by the one-step plasma electrolytic oxidation process. The fabricated TiO2 -based transition metal oxide composites took advantage of the high theoretical capacity of ZnO and the good structural stability of TiO2, showing a high specific capacity (706.2 mAh g −1 over 400 cycles at 0.1 A g −1 ) and a good rate capability (capacity reversible after 2.0 A g −1 ). When the scan rate gradually elevated from 0.2 to 1.0 mV s −1, the pseudocapacitance contribution increased from 63.9% to 81.2%. Besides, the hole-containing morphology of the film guaranteed efficient diffusion and excellent dynamic characteristics for Li  +  . The whole film preparation process was accompanied by a facile in-liquid plasma discharge with an average electron temperature of 3519 K. This high-efficiency and low-cost approach extends the practical territory of transition metal oxide anodes.